Peningkatan Literasi Finansial Anak Melalui Sosialisasi Gemar Menabung Dan Pembuatan Celengan Di Sdn 1 Pupus - Nimas Ayu; Revalina Putri; Sindi Wahyu Rahmasari; Farizki Akbar; Akhdan Ardi (PT Mekar Research and Publishing, 2025)
Financial literacy at an early age is widely recognized as a critical component in shaping responsible economic behavior and fostering long-term financial well-being. This study explores the implementation of a “Save and Create Piggy Bank” program conducted at SDN 1 Pupus on August 19, 2025, involving 47 elementary school students over a duration of 1 hour 30 minutes. The program was designed to increase children’s awareness of the importance of saving and to cultivate practical saving habits through an interactive and hands-on approach. During the activity, students received counseling on financial responsibility, the value of money, and the benefits of saving for future needs. Following the counseling session, students engaged in a creative exercise by decorating and personalizing their own piggy banks, which provided a tangible medium to apply the concepts they had learned. Observations indicated a significant improvement in students’ understanding of saving, enhanced creativity and engagement in the activity, and a demonstrated motivation to maintain regular saving habits beyond the session. The findings suggest that integrating financial education with practical, experiential learning can effectively enhance children’s financial literacy while simultaneously promoting positive behavioral changes. Furthermore, such initiatives may serve as a model for schools and community programs aiming to strengthen financial awareness and responsible money management skills from an early age. This study underscores the importance of early intervention and experiential learning in developing the foundational competencies necessary for lifelong financial capability.